(untitled) (Medico Legal Update, 2020)
In recent years, there have been considerable developments in international law with respect to the normative definition of the right to health, which includes both health care and healthy conditions. These norms offer a framework that shifts the analysis of issues such as disparities in treatment from questions of quality of care to matters of social justice. Building on work in social epidemiology, a rights paradigm explicitly links health with laws, policies, and practices that sustain a functional democracy and focuses on accountability